2011
DOI: 10.1152/ajpregu.00737.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-adrenergic receptor agonists on drinking and arterial blood pressure in young and old rats

Abstract: Thunhorst RL, Grobe CL, Beltz TG, Johnson AK. Effects of ␤-adrenergic receptor agonists on drinking and arterial blood pressure in young and old rats. Am J Physiol Regul Integr Comp Physiol 300: R1001-R1008, 2011. First published February 9, 2011 doi:10.1152/ajpregu.00737.2010.-These experiments examined water-drinking and arterial blood pressure responses to ␤-adrenergic receptor activation in young (4 mo), "middle-aged" adult (12 mo), and old (29 mo) male rats of the Brown-Norway strain. We used isoproteren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In addition, experimental studies find age-related deficits in salt appetite, the companion motivation to thirst, in response to sodium depletion in old rats of the Brown Norway (BN), Sprague-Dawley (SD), and Fischer 344 (F344) strains (5,32,48). The sodium depletion model of salt appetite elicits sodium ingestion in part by causing the release of renal renin in amounts sufficient to generate the high levels of circulating ANG II that promote sodium intake (12,37,46,51). Thus the relative inability of old rats to secrete renin when challenged (1-3, 31, 32, 39, 47) can explain age-related declines in salt appetite following sodium depletion.…”
mentioning
confidence: 99%
“…In addition, experimental studies find age-related deficits in salt appetite, the companion motivation to thirst, in response to sodium depletion in old rats of the Brown Norway (BN), Sprague-Dawley (SD), and Fischer 344 (F344) strains (5,32,48). The sodium depletion model of salt appetite elicits sodium ingestion in part by causing the release of renal renin in amounts sufficient to generate the high levels of circulating ANG II that promote sodium intake (12,37,46,51). Thus the relative inability of old rats to secrete renin when challenged (1-3, 31, 32, 39, 47) can explain age-related declines in salt appetite following sodium depletion.…”
mentioning
confidence: 99%
“…In a series of studies, we observed deficiencies in both osmotic and renin-dependent thirsts in old BN rats (51,52,55,56,60). Notably, the salt appetite response to sodium depletion is greatly reduced-and sometimes absent-in aged rats (3,40,54), even after multiple episodes of sodium depletions (56).…”
Section: Discussionmentioning
confidence: 96%
“…Like the elderly, aged rats show signs of declining thirst, renal function, and cardiovascular responding. Aged rats do not drink as much water as young rats in response to deficits of either intracellular or extracellular water (3,40,51,52,55,56,60). Aged rats have difficulty retaining water and sodium in times of deficit and are slower than young rats to excrete excess water and sodium (1,4,34,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of PRA and aldosterone levels observed after isoproterenol treatment (19) were attenuated in Adriamycin-treated rats providing evidence that the renin-angiotensin system is less responsive to blood pressure/volume-related challenges. This result may account for the decreased water intake after isoproterenol treatment and water deprivation and possibly explains the attenuated water and hypertonic saline intakes after Furo/Cap treatment.…”
Section: Discussionmentioning
confidence: 99%